Stability Indicating RP-HPLC Method Development And Validation For The Simultaneous And Rapid Estimation Of Rosuvastatin And Fenofibrate In Pharmaceutical Dosage Form - Dr. Sushama raju ambadekar; jayesh pandharinath tamhanekar; vijay arjun bagul (International Journal of Pharma and Bio Sciences, 2022)
The objective of this research is to develop fast, simple, specific, linear, precise, accurate and stability indicating reverse phase liquid chromatographic method for the simultaneous determination of Rosuvastatin and Fenofibrate in tablet dosage forms. The chromatographic separation of Rosuvastatin and Fenofibrate peaks was achieved using YMC-Ultra HT Pro C18 (100 mm x 2.0 mm, 2 µm particle size) column. Mobile phase composed of buffer and acetonitrile (30:70 v/v) was selected and a flow rate of 1.2 mL/minute is monitored with injection volume of 20 µl. Column oven temperature and autosampler temperature was maintained at 25ºC. Detection was carried out at 240 nm. The method was validated as per International Council on Harmonization (ICH) guidelines. The drugs were subjected to acid, base, oxidation, hydrolysis, photolysis and thermal degradation. Linearity range was observed in concentration range of 5.792 μg/mL to 17.376 μg/mL for Rosuvastatin and 80.165 μg/mL to 240.495 μg/mL for Fenofibrate. The percentage recovery for Rosuvastatin and Fenofibrate was observed as 101.3% and 101.8% respectively. The correlation coefficient for both the components was close to 1. System suitability criteria was also fulfilled. This method is specifically developed for rapid and simultaneous estimation of Rosuvastatin and Fenofibrate having a shorter run time of 6 minutes. The retention time for Rosuvastatin and Fenofibrate was reduced to 0.75 and 3.46 minutes respectively. Hence developed reverse phase high-performance liquid chromatography (RP-HPLC) method is simple, fast and economical. Impurities resulting from the stress studies did not interfere with the detection of assay of Rosuvastatin and Fenofibrate thus it is stability-indicating. The projected method can be utilized for routine analysis in the quality control department from the pharmaceutical industry.